Ultimate Population Size under Changed Age Specific Fertility Schedule - Aryal, Roshan; Aryal, T.R. (Journal of Institute of Science and Technology, 2015)
This paper attempts to obtain ultimate population size under changed age specific fertility schedule. The reduction in fertility under exponential and linear decline has been discussed in order to obtain ultimate population size. A concept has been suggested to obtain ultimate population size by combining both exponential and linear decline pattern in age schedule due to faster reduction in fertility at the beginning and thereafter slower declining rate in fertility age schedule. Journal of Institute of Science and Technology, 2015, 20(1): 138-140